Results of Traditional Manual Therapy on Lower Back Pain as an Alternative to Aggressive Therapy - R. Molor; G. Odontsetseg; D. Tseendagva (Креативная хирургия и онкология)
Introduction. In briefly to have eight symptoms of Qi disease and very common one which is including all symptoms is Lower back pain. By the WHO research pain here can be intense and is one of the top causes of missed work. This disease has very painful, recurrence and needs period of treatment time, cost expensive. Most of the damages for patients are diagnosis, surgery, pain relief medicines. Thus, we made this theory with practice research on traditional manual therapy for qi originated Lower back pain. Purpose: to compare the traditional diagnostic methods of manual therapy and modern diagnostic methods of X-ray with lower back pain by using assessment of a quality of life developed by WHOQOL.Materials and methods. 100 patients with lower back pain were examined. The treatment results were evaluated after the application of traditional rhythmic vibration therapy. These treatment results were obtained using traditional diagnostic methods and using radiography of the lower back, which were compared with each other. The WHOQOL questionnaire was used to assess quality of life.Results and discussion. Therapy was carried out for 10 days. Manual therapy has shown its positive results within a day. Although the anatomical and morphological structure of the lower back showed no significant improvement within 7-10 days of treatment (75 %), but the space of the spine increased (80 %), and spinal mobility was asymptomatic (90 %).Conclusion. Patients treated with manual therapy symptomatically recovered after a year (60 %). Of 100 patients, they were completely cured by 15 % and improved by 30 %.